Role of gamma-aminobutyric acid (GABA) in hypothalamic nuclear development - McClellan, Kristy Michelle, author; Tobet, Stuart A., advisor (Colorado State University. Libraries, 2008)
The hypothalamus is involved in energy balance, appetite regulation, stress and anxiety, reproduction including sex behavior, and aggression. It is divided into cell groups based on cell staining, functional similarities and projections. This dissertation looks at the development of three of these cell groups, the ventromedial nucleus (VMN), the paraventricular nucleus (PVN), and the arcuate nucleus (ARC). The VMN and PVN have a unique pattern of GABA expression in elements surrounding the nuclei, with a void of GABA within the region of the developing nuclei. The ARC, on the other hand, has dense GABAergic immunoreactive elements throughout the nucleus. Because of the expression pattern of GABA immunoreactivity surrounding the VMN and PVN, it is likely that GABA is acting as a boundary cue to influence migrating neurons. Chapter 2 reviews the development of the VMN, including a discussion of the heterogeneity of the nucleus, a description of what cues are involved in cell migration, and descriptive information on the directions of cell movement during development. Chapter 3 examines the role of GABA on cell migration within the VMN and ARC. A live slice culture system allowed visual tracking of cell movement in the VMN and ARC. There was a difference between the average movement speeds of cells in the VMN vs. cells in the ARC, and upon addition of GABA receptor antagonists to the slices, VMN cells increased in speed while ARC cells did not change. In mice lacking functional GABAB receptors there was a change in cell positions of neurons containing immunoreactive estrogen receptor (ER)α, which may be due to changes in cell movements and migration. There was no change in amount of cell positions of immunoreactive ERα cells in the ARC. Chapter 4 looks at the role of GABA and brain derived neurotrophic factor (BDNF) in PVN development. There was a sex-selective effect in GABAB R1 subunit knockout mice of positions of cells containing immunoreactive ERÎα, indicating that females may be particularly more susceptible to changes in GABA signaling as it may be influencing the final positions of cells. There was also a decrease in BDNF expression in GABABR1 subunit knockout mice, suggesting that GABA may play a role in cell differentiation. In conclusion, several lines of evidence indicate roles for GABA in the development of the hypothalamus, in particular, within the VMN and PVN.
Keywords: GABA; hypothalamus; nuclear development; molecular biology